2001
DOI: 10.1074/jbc.m009728200
|View full text |Cite
|
Sign up to set email alerts
|

Human Nod1 Confers Responsiveness to Bacterial Lipopolysaccharides

Abstract: The immune response to microbial pathogens is initiated by recognition of specific pathogen components by host cells both at the cell surface and in the cytosol. While the response triggered by pathogen products at the surface of immune cells is well characterized, that initiated in the cytosol is poorly understood. Nod1 is a member of a growing family of intracellular proteins with structural homology to apoptosis regulators Apaf-1/Ced-4 and a class of plant disease-resistant gene products. Here we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
355
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(372 citation statements)
references
References 24 publications
13
355
0
3
Order By: Relevance
“…N-myristoyl (C 14 ) ␥-D-glutamyl-meso-diaminopimelic acid (iE-DAP; in a modified form denoted KF1B), a Nod1 activator, has been described (17). The amount of Nod1 and Nod2 stimulatory activity in LPS preparations was determined as described (15,18) and given as units per microgram of weight. One unit of the Nod1 and Nod2 stimulatory activity is equivalent to that of 1 ng of synthetic iE-DAP and MDP, respectively.…”
Section: Reagents and Bacterial Culturementioning
confidence: 99%
See 1 more Smart Citation
“…N-myristoyl (C 14 ) ␥-D-glutamyl-meso-diaminopimelic acid (iE-DAP; in a modified form denoted KF1B), a Nod1 activator, has been described (17). The amount of Nod1 and Nod2 stimulatory activity in LPS preparations was determined as described (15,18) and given as units per microgram of weight. One unit of the Nod1 and Nod2 stimulatory activity is equivalent to that of 1 ng of synthetic iE-DAP and MDP, respectively.…”
Section: Reagents and Bacterial Culturementioning
confidence: 99%
“…These studies suggested that RICK is involved in TLR signaling. However, many preparations of bacterial components contain Nod1-and Nod2-stimulating molecules (4,5,7,15,16) and the presence of such contaminants could also explain reduced TLR signaling in RICK-deficient macrophages. In the present report, we have studied the role of RICK in TLR signaling in macrophages and in the animal.…”
mentioning
confidence: 99%
“…The total RNA was converted to cDNA and QPCR was performed to determine the number of copies of IL-8. For Nod studies, experiments examining the synergistic activation of NF-B by c-di-GMP in cells overexpressing Nod1 or Nod2 were conducted as previously described (32). Briefly, HEK 293 T cells were transfected overnight with 30 ng of Nod1 or Nod2 plus 75 ng of Ig luciferase reporter plasmid.…”
Section: Tlr and Nucleotide-binding Oligomerization Domain (Nod) Studiesmentioning
confidence: 99%
“…When indicated, cells were also cotransfected with pcDNA3-p53, pcDNA3-Gfi (both provided by G. Nunez, University of Michigan, Ann Arbor, MI), pRc/CMVp65 (provided by I. Udalova, University of Oxford, U.K.), pcDNA3-Stat3C (17), pcDNA3-E2F1 (18), or pcDNA3 empty vector. In another set of experiments, HEK293T cells were cotransfected with NLRP2 cDNA cloned into pHA-EAK vector (15), 0.25 g of the reporter plasmid pBVIxLuc, containing six NF-B recognition sites within the promoter sequence linked to the luciferase gene (19), and 0.2 g of pRSV-␤-galactosidase. Polymorphic variants of NLRP2 were generated by site-directed mutagenesis of the pHA-EAK-NLRP2 vector (15) with 18-bp primers containing the nucleotide change in the middle of the sequence.…”
Section: Transfections and Gene Reporter Assaysmentioning
confidence: 99%